Comparison of antibody responses of heterologous and homologous Covid-19 booster vaccination: an observational study - Rizvi, Nayab Batool; Bibi, Maryam; Rana, Muhmmad Zeeshan; Zaffar, Sehrish; Farooq, Hassam (Frontiers in Immunology, 2024)
Objective: Pakistan has been seriously affected by the COVID-19 pandemic, with numerous waves of infection. Using different vaccine and booster doses was a key component to control and combat this pandemic. This study aims to monitor the heterologous and homologous booster vaccination doses that generate immune responses in healthy adults after 9 months of vaccination.In this cross-sectional, observational study a total of 173 samples were collected.Participants from both genders (Male and Female) between the ages of 18 to 25 years were enrolled for the study. Participants who had booster shots of homologous Sinopharm BBIBP CorV and heterologous Pfizer-BioNTech vaccines were included only, with the use of a Roche Cobas-e601 analyzer, the antibody titers in the blood serum were quantified by the ECLIA method. IBM SPSS 22 was utilized for descriptive statistical analysis and P< 0.05 was considered significant.In this study the IgG antibody levels were measured against the full length of receptor binding domain (RBD) of the spike (S) protein. The mean antibody titer in the Pfizer group was 9764±10976 U/mL and 5762±4302 U/mL in the Sinopharm group. The Mean IgG antibody levels of the Pfizer-vaccinated group were significantly higher than the Sinopharm-vaccinated group (P=0.000, each). Comparing the Sinopharm BBIBP CorV booster dosage to the Pfizer booster, Pfizer BNT162b2demonstrated a stronger immune response. However, there were no immunological gender-specific significant differences. The administration of a third dosage of Pfizer BNT162b2 after two doses of BBIBP CorVThe administration of a third dosage of Pfizer BNT162b2 after two doses of BBIBP-CorV is recommended to boost the humoral immune response in the general population while there was no gender-specific difference observed. More effectiveness can be attained by administering additional doses due to the antibody decay.